1997
DOI: 10.1093/ajcp/107.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Isolated 13ql4 Abnormalities and Normal Karyotypes Are Associated With Typical Lymphocyte Morphology in B-Cell Chronic Lymphocytic Leukemia

Abstract: Peripheral blood lymphocyte morphology and karyotype were correlated across the spectrum of cytogenetic abnormalities in 78 previously karyotyped cases of B-cell chronic lymphocytic leukemia (CLL). Cases were classified according to FrenchAmerican-British morphologic criteria as typical CLL or CLL, mixed-cell type; the latter category was divided into CLL with a mixture of small and large cells and CLL with increased prolymphocytes (CLL/PL). Other leukemic lymphoproliferative disorders were excluded from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 83%
“…This finding was somewhat unexpected in light of several studies that have shown an apparent correlation between morphology and immunophenotype (65)(66)(67)(68)(69)(70)(71). In addition, CLL with trisomy 12 has been associated with atypical morphology (65)(66)(67)(68)(69)(70)(71). Furthermore, cases of CLL with trisomy 12 have been shown to be associated with an atypical immunophenotype including increased CD20 expression (66,70) and expression of FMC7 (65,68,70,71).…”
Section: Comparison Of Cases With Two Samples From the Same Patientmentioning
confidence: 88%
“…Most of the Correspondence: F Ajchenbaum-Cymbalista; Fax: 33 1 42 34 82 54 Received 7 January 1998; accepted 20 April 1999 studies conducted on atypical B-CLL have been devoted to their immunologic characteristics 2,3 or to cytogenetic abnormalities, [4][5][6][7][8][9][10][11] but clinical presentation and outcome have not been extensively studied, although they are considered as sharing a poorer prognosis than typical CLL. 12 Among the recurrent genetic alterations observed in B-CLD, the translocation t (11;14) has been recently highlighted, since it is the hallmark of MCL.…”
Section: Introductionmentioning
confidence: 99%
“…When single cytogenetic abnormalities are examined, trisomy 12 is associated with shortened survival, whereas isolated abnormalities of chromosome 13q14 are associated with favorable outcomes, comparable to those of patients lacking clonal chromosome abnormalities [2]. Previous studies suggest that the morphologic and immunophenotypic variation observed in B-CLL is also related to karyotype [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%